Hubungan Dukungan Sosial Teman Sebaya Dan Aktualisasi Diri Dengan Harga Diri Remaja Panti Asuhan Di Purbalingga - Muhammad Muharrik As Sururi; Muslikah Muslikah (Universitas PGRI Semarang, 2020)
Teenagers in orphanages experience low self-esteem compared to adolescents who live with their parents. Factors that influence the level of self-esteem include peer social support and self-actualization. This research is to find out the relationship between social support of peers and self-actualization with the selfesteem of teenagers at the Orphanage in Purbalingga. The method used is quantitative, with using purposive sampling techniques and data analysis techniques is multiple regression. The results showed (1) there was a positive and significant relationship between peer social support and adolescent self-esteem in the Orphanage in Purbalingga (p = 0,000, β = 0.444) (2) there was a positive and significant relationship between self-actualization and adolescent self-esteem Orphanage in Purbalingga (p = 0,000, β = 0.728) (3) there is a significant relationship between peer social support and self-actualization with adolescent self-esteem in Purbalingga Orphanage (p = 0,000, R = 0.704, F = 47,690). From the results of the study it can be concluded that the higher the social support of peers, the higher the self-esteem of adolescents, the higher the self-actualization, the higher the adolescent self-esteem, and the higher the social support of peers and self-actualization, the higher the selfesteem of adolescents.